Relationship between Body Composition and Serum Immunoglobulin Concentrations after Administration of Intravenous Immune Globulin-Preclinical and Clinical Evidence - Luigi Brunetti; Helene Chapy; Ronald G. Nahass; Rebecca Moore; Andrew Wassef; Derek Adler; Edward Yurkow; Leonid Kagan (MDPI AG, 2023)
The purpose of this study was to investigate the effect of obesity on immunoglobulin G (IgG) pharmacokinetics in a rat model of obesity, and to collect clinical evidence for an association between the body composition and intravenous immune globulin (IVIG) pharmacokinetic parameters in humans. In a preclinical study, pharmacokinetics of human IgG was evaluated after intravenous (IV) and subcutaneous (SC) delivery to obese and lean rats (n = 6 in each group). Serial serum samples were analyzed using an ELISA. The animal body composition was assessed using computer tomography. Patients with primary immunodeficiency currently managed with IVIG, and at a steady state, were enrolled in the clinical study (n = 8). Serum immune globulin (Ig) concentrations were measured at baseline and immediately after the administration of two consecutive treatments, with an additional measurement at two weeks after the first administration. In addition to the patient demographic and clinical characteristics, body composition was measured using bioelectrical impedance analysis. The pharmacokinetics of human IgG was significantly different between the obese and lean rats after both the IV and SC administration of 0.5 g/kg. Furthermore, a significant difference in endogenous rat IgG was observed between the two strains. In the human study, total serum IgG and subtype (IgG1, IgG2, IgG3, IgG4) half-life negatively correlated with the body mass index and fat mass. The mean change in the total serum IgG concentration was significantly correlated to body mass index and fat mass. The results of the studies corroborated one another. In the animal study, most pharmacokinetic parameters of human IgG following IV and SC administration were significantly affected by obesity and changes in the body composition. In the clinical study, the mean serum IgG change after the IVIG administration strongly correlated to the BMI and body fat mass. Future studies are needed to establish the outcomes achieved with more frequent dosing in obese individuals with primary immunodeficiency.